Endoscopic Sciatic Neurolysis for Deep Gluteal Space Syndrome - Nicholas A. Trasolini MD; Morgan Rice BS; Katlynn Paul BS; Shane J. Nho MD, MS (SAGE Publishing, 2022)
Background: Deep gluteal syndrome (DGS) encompasses a spectrum of pathologies causing symptomatic sciatic nerve compression deep to the gluteus maximus muscle. Endoscopic sciatic neurolysis is an option for management of DGS when conservative treatment fails. Indications: Endoscopic sciatic neurolysis is indicated for retro-trochanteric pain, sciatica-like burning in the posterior thigh, and sitting discomfort that is reproducible on physical examination after failing conservative management. Technical Description: The technique presented here introduces a standard endoscopic sciatic neurolysis technique with an accessory posterolateral portal placed distally and in line with the sciatic nerve. Use of a switching stick through an accessory distal posterolateral portal can allow for in-line protection and retraction of the sciatic nerve while it is carefully released from compressive fibrous bands using an arthroscopic shaver. It is important that the accessory portal be placed under direct visualization with caution not to injure the sciatic nerve. An arthroscopic radiofrequency device can be used for hemostasis and further release of fibrous bands. At the end of the procedure, the sciatic nerve should be visualized fully released and freely mobile from the piriformis muscle to the level of the lesser trochanter. Results: In properly selected patients, the procedure is very successful. In a series of 35 cases, the procedure reduced sitting pain (present in 97% of patients preoperative, 17% of patients postoperative), reduced narcotic use, improved visual analog scale (VAS) pain scores, and improved modified Harris hip scores without major complications. Discussion: Although rare following hip arthroscopy, postoperative scarring and fibrous bands are a common cause of DGS which can be effectively treated by endoscopic sciatic nerve decompression. Results of endoscopic sciatic neurolysis have thus far been encouraging with improvements in patient reported outcome scores and high rates of satisfaction. However, complications do occur and can result in neurologic deficits. Nevertheless, with careful patient selection and meticulous sciatic nerve dissection, endoscopic sciatic neurolysis for DGS is a safe and effective technique for decompression of fibrous bands and adhesions that can lead to sciatic neuralgia.